Evaluación agro-morfológica y productiva de 9 cultivares de Café Arábigo (Coffea arabiga I) en el tercer año de cultivo en el cantón Caluma, provincia Bolívar-Ecuador - Velásquez Velásquez, Jonathan Francisco (2017)
Research on agro-morfologica and productive evaluation of 9 cultivars of arabica coffee (Coffea Arabica l.) in the third year of cultivation, in canton Caluma, Bolívar province, Ecuador, had as targets; 1) Identify cultivars of arabica coffee that the best agronomic, morphological and productive characteristics for this agro-ecological zone; 2) To assess the incidence of pests and diseases in nine cultivars of arabica coffee in the Experimental Farm El Triunfo of Caluma and 3) Determine the physical quality and organoleptic nine cultivars of Arabica coffee in post harvest. The study was conducted in the Experimental Farm of El Triunfo of the Universidad Estatal de Bolivar in varieties Pache, Catuai rojo, Bourbon, Catuai amarillo, Catimor 02, Catimor 01, Sarchimor 4260, Sarchimor 1669-02 and Sarchimor 1669-01 during the third year of establishment. Statistical analysis used in this study was quantitative and data were evaluated with descriptive statistics, analysis of variance, correlation analysis, linear regression, and for the separation of means was performed through Tukey analysis Among the results obtained indicated that Bourbon record the highest plant and Pache was the variety with less height. Sarchimor 1669-01 and Bourbon varieties recorded the lowest of several fruits. As regards presence of rust of the coffee tree, the varieties Catuaí rojo, Catuai amarillo, Bourbon, and Pache were susceptible to this disease; Unlike Sarchimor 4260, Sarchimor 1669-01, Sarchimor 1669-02, Catimor 01 and 02 Catimor which no reported incidence of rust With respect to the physical variables of grain size was similar in varieties in the study, they recorded more than 90% above the shale 15, for the density of the grain variety Pache was that record the lowest value of the variable and recorded an effective conversion of green coffee to roast coffee (> 80%). In terms of sensory analysis the Pache obtained the highest value scoring 87.5 points which gives it a category of specialty coffee. However indicated that each variety emphasize in their attributes by register fragrance light almond, walnut, roasted coffee, chocolate, fresh xviii fruit, honey, brown sugar; with light body medium and creamy; flavors of tropical fruit, nuts, chocolate; with low to medium acidity, citrus and malica